Planejamento da produção e projeto de uma unidade de fabricação de produtos destinados à higiene pessoal - Cruz, Soraya Almeida Andrade (2011)
The vast majority of chemical products, both in number and volume, are produced by batch processes. Recent studies show that only six percent of the batch processes were satisfactorily replaced by continuous processes. This clearly shows the importance and permanence of such processes. These plants have a basic characteristic of intermittent production of a product with non-stationary operation, including steps of loading, processing, cleaning and drainage, what makes the project complex. Its use is recommended, or for technological reasons or to meet the need for a dynamic and uncertain market, as it is the case of products with high added value and small demand. An important aspect of this type of plant is its flexibility in producing multiple products in a unique plant. The batch operations are economically justified when a large number of products are produced using similar production paths. Due to the difficulty of predicting the peak and the extension of demand, such settings are frequently modified plant and equipment is usually small and versatile and can be used by a large number of products. Power must be flexible enough to adapt to market needs and product life cycle is usually short. Brazil ranks third in world ranking in sales of personal care products, perfumes and cosmetics. The industry in this sector, in the two study reaches, each year, more consumers. The currently complex and competitive global market requires that companies seek to optimize processes, reduce costs and achieve economies of scale. In view of this, we have the developed a mathematical model of large, from real data, obtained in a Personal Hygiene Industry, providing a practical application to the work on Design and Production Scheduling of Multipurpose Batch Plants, from Professor João Soletti, which enables to perform planning and design of this type of plants.